IMPLEMENTATION OF THE PRINCIPLE OF ULTRA PETITUM PARTIUM IN DECIDING CHILDREN LIVELIHOOD IN DIVORCE LAWSUIT IN RELIGIOUS COURTS - Hotnidah Nasution (AHKAM : Jurnal Ilmu Syariah, 2018)
This study analyzes 64 decisions of the South Jakarta Religious Courts, issued in 2011-2013, to see how ultra petitum partium principle is used to settle a child support claim in a divorce case. Child protection lawsuit is a legal solution given by the law to force fathers to carry out their obligations to fulfil their children's livelihood. In the Religious Courts, the case can be done simultaneously with a divorce case or done separately. In this study, the author argues that in deciding children’s livelihood claims, judges in the Religious Courts, besides having to comply with the applicable procedural law, should also follow basic principles applied in the General Court.  This is based on article 54 of Law No. 7 of 1989 (amended by Law No. 3 of 2006 and Law No. 50 of 2009). One of the principles is ultra petitum partium, in which the judges are prohibited from deciding a matter that is not stated in the lawsuit or decide more than what is demanded. From 64 decisions, 60 of them applied the ultra petitum partium principle. In this case, none of them decided to order the fathers to pay for children supports, even though the posita mentions that children were born during their marriage, and the children are with the mothers.